LAW-LANGUAGE: THE CHALLENGE OF THE CAVEAT ‘WHENEVER REASONABLY PRACTICABLE’ IN LANGUAGE POLICIES - Montle, Malesela; Kekana, Tebogo Johannes (Universitas Islam Sumatera Utara (UISU), 2024)
The challenge of escape clauses in various policies has been a longstanding issue for policy scholars worldwide. This challenge is also prevalent in South African institutions, particularly in their language policies. This article reports on the findings of a desk-based investigation into the escape clause